Work values and job satisfaction: A qualitative study of Iranian nurses - Ravari, Ali (Nursing ethics, 2013)
This study aimed to describe the effect of nursing profession work-related values on job satisfaction among a sample of Iranian nurses. We used in-depth interviews with 30 nurses who worked in university-affiliated and public hospitals in Tehran, Iran. The results of thematic analysis of interviews are reported in four themes to present the participants’ articulations in linking their work-related values to job satisfaction. The themes consist of values that “encourage tolerance,” “enhance inner harmony,” “reflect traditional commitment,” “enhance unity,” and are “centered around altruism and spiritual values.” The most satisfied participants considered nursing a divine profession and a tool by which they could gain spiritual pleasure and satisfaction. Our findings highlight the potential role of nursing work-related values in reducing dissatisfaction with one’s job. For the nursing profession, this may have implications in reducing job instability and turnover.